About cooperative engineering: theory and emblematic examples. Issue 1 (1st January 2017) - Morales, Grace; Sensevy, Gérard; Forest, Dominique
Abstract: In this article we focus on 'cooperative engineering', in which teachers and researchers co-design didactic sequences. In the first part of the article, we present cooperative engineering by describing some of the main principles on which it is grounded. The second part is dedicated to a case study, which enables us to illustrate some elements of the collective work in a specific cooperative design in kindergarten. The designed learning game, the 'Treasure Game', aimed to assist kindergarten students to build a system of graphical representations, which was implemented in a series of phases in which students were asked to memorise a series of items with increasing levels of difficulty. The game demonstrated the students' growing competence in recalling items using strategies such as making lists and working collaboratively to collectively recall items through a 'treasure box'. In the third part of the article, we show how this case study embodies some of the main principles put forward in the first part.